How researchers shape the construction of landscape change – insights from a scenario study. (17th November 2021) - Knierim, Andrea; Bieling, Claudia; Zander, Peter
ABSTRACT: Studying landscape change has taken on increased importance, for instance, in the context of enhancing the sustainable intensification of agricultural production. As sustainability-oriented landscape research necessitates inter- and transdisciplinary approaches, the influence that researchers exert through constructing and applying conceptual bases and methods merits particular attention. We address this issue with a multifaceted understanding of power, and apply three analytical lenses to the example of a regional, landscape-related scenario study. We found that without an interdisciplinary framework that fosters integration and explicit cooperation procedures, researchers exert individual 'power to' by adhering to well-known disciplinary methods. Also, we observed a mobilisation of 'power with' through a certain level of transdisciplinary cooperation. We recommend a rigorous specification and application of joint conceptual bases, their disclosure and an ongoing reflection on inter- and transdisciplinary cooperation procedures to ensure the transparency of researchers' influence in studies on landscape change.